Revealing tribo–oxidation mechanisms of the copper–WC system under high tribological loading. (November 2021) - Chen, X.; Ma, Y.; Yang, Y.; Meng, A.; Han, Z.X.; Han, Z.; Zhao, Y.H.
Abstract: The near-surface structural and chemical changes were investigated for pure copper against a tungsten carbide (WC) sphere during high tribological loading. Fundamental stages are identified in the Cu-WC tribo-system: (i) high tribological stress promotes grain refinement to the ultra-fine grains regime in the very beginning; (ii) nucleation of extremely fine ( 3 nm) oxygen–enriched Cu nano particles in the near-surface layer and subsequent growth of the Cu2 O oxide; (iii) formation of continuous nanostructured mixing layer with heterogeneous Cu and O distribution in the late stage. Near-surface mechanical mixing is presumably the main contribution to chemical modifications under high tribological loading. Our findings shed atomic-insights into intricate tribochemical modifications, one of the most intriguing phenomena in material-oriented tribology. Graphical Abstract: Image, graphical abstract